Deteksi Kesehatan Mental Remaja Di Masa Pandemi Covid-19 Pada Santri Pondok Al Fiel Kesugihan Kabupaten Cilacap - Intan Diah Pramithasari (JPS : Jurnal Pengabdian Serulingmas, 2022)
The Corona Virus Disease (Covid-19) outbreak has had tremendous effects on physical and mental health. One of the groups who feel the psychological impact of the Covid-19 pandemic is teenagers. During the Community Activity Restriction Program, there was a policy of teaching and learning processes carried out at home via distance. This condition can lead to several psychological problems that occur in adolescents such as anxiety, stress, or depression. The purpose of this community service is to increase youth's understanding of the importance of maintaining mental health both during the pandemic and in later life. The methods used in this community service are lectures and discussions, in addition to knowing the initial description of the mental health level of adolescents at Al Fiel Islamic Boarding School, a survey was conducted using the Strength and Difficulties Questionnaire (SDQ) questionnaire. The results of this community service activity were very enthusiastic for students to take part in the activity as evidenced by the many questions asked in the discussion session. In addition, from the detection results, it was found that 2.94% of adolescents experienced prosocial problems, 17.6% emotional problems, 8.8% behavioral problems, 32.3% hyperactivity, and 29.4% relationship problems with peers. From these results, it can be said that the purpose of community service has been achieved.